2011
DOI: 10.1159/000322591
|View full text |Cite
|
Sign up to set email alerts
|

Delirium Is an Important Predictor of Incident Dementia among Elderly Hip Fracture Patients

Abstract: Background: Delirium is believed to constitute a risk factor for dementia, but previous research has failed to satisfactorily take account of the patients’ preexisting level of cognitive functioning. Methods: A prospective 6-month follow-up of 106 elderly hip fracture patients free from prefracture dementia. Delirium was assessed by the Confusion Assessment Method. Caregivers described the patients’ prefracture cognition by the Informant Questionnaire on Cognitive Decline in the Elderly, Short Form (IQCODE-SF)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
64
1
9

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(81 citation statements)
references
References 73 publications
6
64
1
9
Order By: Relevance
“…For example, when elderly patients become delirious during infections, treatment of the infection may go well but the patients emerge with dementia. Similar observations have been made after postoperative delirium in elderly hip fracture patients free from preexisting dementia [97,98]. Other studies have shown that new episodes of cognitive decline in AD cases were concomitant to systemic inflammatory events [99,100].…”
Section: The Microglia Priming Hypothesissupporting
confidence: 72%
“…For example, when elderly patients become delirious during infections, treatment of the infection may go well but the patients emerge with dementia. Similar observations have been made after postoperative delirium in elderly hip fracture patients free from preexisting dementia [97,98]. Other studies have shown that new episodes of cognitive decline in AD cases were concomitant to systemic inflammatory events [99,100].…”
Section: The Microglia Priming Hypothesissupporting
confidence: 72%
“…However, over the 48-hour observation period we collected several sources of information, so this error is probably negligible. Another potential source of misclassification bias relates to the criteria used to define SSD in a population like ours, very complex and with a high prevalence of cognitive impairment and dementia (there may be an overlap of symptoms between SSD and dementia) and delirium is an important predictor of incident dementia [28]. There could also be a possible overlap of symptoms between SSD and dementia.…”
Section: Discussionmentioning
confidence: 94%
“…With 402 patients included in this prospective, observational study, the number of patients investigated is large compared with that of other single-center studies on this topic [20,33,34]. The predominantly female cohort included in this series is typical for a geriatric patient population with a comparatively high ASA score at hospital admission [35,36,37].…”
Section: Discussionmentioning
confidence: 99%